Remote Detection of Oil Slicks at the Ocean Surface - Gallegos, Sonia C; García-Pineda, Oscar; Pichel, William; Kukhtarev, Nickolai; Kukhtareva, Tatiana; Armstrong, Duane (UD y la Geomática, 2015)
The 2010 Deepwater Horizon (DWH) oil slick caused by the explosion of the Macondo well was the worst man-made disaster in the history of the Gulf of Mexico, and the largest marine spill in the history of the petroleum industry. We provide an overview of our efforts to monitor the extent of these slicks using automated algorithms for the Moderate Resolution Imaging Spectroradiometer (MODIS), and the Synthetic Aperture Radar (SAR). We discuss the advantages and limitations of each of the methods in detection of oil from space, and suggest that the NIR bands may be the best option to monitor emulsified oil when using passive sensors. Additionally, we discuss current laboratory-based efforts to measure oil thickness via holographic interferometry, and propose this as an ideal technique for future remote sensing of oil.